Facial Features Detection and Face Emotion Recognition: Controlling a Multimedia Presentation with Facial Gestures - Ajanovski, Vangel (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University - Skopje, Macedonia, 2002)
Facials features detection fits into the area of computer vision, with a special focus on the problem of identifying and locating facial features in eyes, nose, mouth, ears etc., in an image or video. This paper presents an application of such techniques in the field of humane interfaces design, and the ability to control a multimedia presentation while only using facial gestures.
Keywords: computer vision, face identification, facial features detection